Study The Rate Constant of Photodecomposition of Polystyrene Films in Presence of Some 4- amino-5-(2-(6-methoxynaphthalen-2-yl)piperidino)-1,2,4-triazole-3-thion Complexes - Awad, Adil A; Al-Hasan, Rehab A M; Yousif, Emad A (Al-Nahrain Journal of Science, 2018)
The photostabilization of polystyrene (PS) films by (4-amino-5-(2-(6-methoxynaphthalen-2-yl)piperidino)-1,2,4-triazole-3-thion(L) compounds was investigated. PS films containing concentration of complexes 0.5% by weight were produced by the casting method from chloroform as a solvent. The photostabilization activities of these compounds were determined by monitoring the carbonyl and hydroxyl indices with irradiation time. The photostabilization of PS films by prepared complexes was investigated. The PS films containing concentration of complexes 0.5% by weight were produced by the casting method from (CHCl3) solvent. The photodegradation of the obtained films was investigated using UV-vis. spectra. The photostabilization activity of these compounds was determined by calculating the photodecomposition rate constant (kd) for the modified PS.